About how, in the heat of battle, a mediator says "Let's talk about it!" and, for some strange reason, the combatants, arms raised to fight, drop their posture and their weapons to listen -this is no movie for men - Fernández Porta, Eloy (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This text focus on various cinematographic works documentaries, and films principally, but also musicals, sociological studies, photographic montage, philosophical works, theater, and news –to highlight the masculine subjectivity that inhabits them–. Talking like a man today, calling oneself a man, and acting like a man, is different today than calling oneself a man, and acting as such, two, three or more decades ago. This text, this author, claim the current world is emptied of masculinity
Keywords: subjectivity; genre; masculinity; mediation; body